Fundamentals of Semiconductors Physics and Materials Properties - Yu, Peter Y.; Cardona, Manuel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
This fourth edition of the well-established Fundamentals of Semiconductors serves to fill the gap between a general solid-state physics textbook and research articles by providing detailed explanations of the electronic, vibrational, transport, and optical properties of semiconductors. The approach is physical and intuitive rather than formal and pedantic. Theories are presented to explain experimental results. This textbook has been written with both students and researchers in mind. Its emphasis is on understanding the physical properties of Si and similar tetrahedrally coordinated semiconductors. The explanations are based on physical insights. Each chapter is enriched by an extensive collection of tables of material parameters, figures, and problems. Many of these problems "lead the student by the hand" to arrive at the results. The major changes made in the fourth edition include: an extensive appendix about the important and by now well-established deep center known as the DX center, additional problems and the solutions to over fifty of the problems at the end of the various chapters. Some of the solutions contain extensions via discussion about topics of current interest in the field of semiconductor physics, such as spin-orbit coupling and k-linear band dispersion.
Electronic Band Structures -- Vibrational Properties of Semiconductors, and Electron-Phonon Interactions -- Electronic Properties of Defects -- Electrical Transport -- Optical Properties I -- Optical Properties II -- Photoelectron Spectroscopy -- Effect of Quantum Confinement on Electrons and Phonons in Semiconductors.
Keywords: Engineering; Electronics; Optical materials; Materials Science; Optical and Electronic Materials; Condensed Matter Physics; Electronics and Microelectronics, Instrumentation; Engineering, general